Exosomal AFAP1-AS1 binds to microRNA-15a-5p to promote the proliferation, migration, and invasion of ectopic endometrial stromal cells in endometriosis - Xi Wang; Mengmeng Zhang; Liaofei Jiang; Xiaoling Fang; Tingting Zhang (BMC, 2022)
Abstract Background Endometriosis (EMS) remains a major challenge to reproductive health due to multifactorial etiology, disease heterogeneity, and the lack of appropriate diagnostic markers and treatment. Eexosome (Exo) has become a major factor in progression of a variety of diseases. However, the mechanisms directing their role in the pathophysiology of EMS are ill-defined. Here, we aimed to investigate the clinical implications of actin filament associated protein 1-Antisense RNA 1 (AFAP1-AS1) in EMS. Methods Bioinformatics analysis was used to predict the expression and interaction of AFAP1-AS1, miR-15a-5p and BCL9 in EMS, and dual luciferase reporter assay was used to verify the targeted relationship of AFAP1-AS1, miR-15a-5p, and BCL9. The Exo from endometrial stromal cells (ESCs) was isolated and characterized by transmission electron microscopy (TEM) and Nanoparticle tracking analysis (NTA). Exosome uptake studies were performed. For in vitro assay, ectopic ESCs (EcESCs) proliferation, migration, and invasion were assessed by CCK-8 and Transwell assays. In vivo assay was performed by establishment of EMS mice to validate the result derived from in vitro assay. Results The Exo was successfully isolated from ESCs and we observed high expression of AFAP1-AS1 and BCL9 but low expression of miR-15a-5p in EMS. Moreover, Exo derived from EcESCs could deliver AFAP1-AS1 to EcESCs and thus promoting proliferation, migration, and invasion of ESCs. AFAP1-AS1 bound to BCL9, which was targeted by miR-15a-5p in EMS. In vivo experiments in nude mice revealed that inhibition of Exosomal AFAP1-AS1 suppressed migration and invasion of EcESCs through miR-15a-5p/BCL9. Conclusions Collectively, these findings suggested that ESCs-derived Exo carrying AFAP1-AS1 contributed to EMS pathogenesis. This study might help us realize the etiology of EMS and improve the treatment of the related complications.